Inverse Modified Z-Transform with Unknown Delay Parameter - R. Z. Akhmetsafina (Известия высших учебных заведений России: Радиоэлектроника)
An algorithm for inverse modified z-transform with delay is considered. The delay parameter is a fraction of the sampling period. The fractional part of the delay is computed as the solution of the equation representing the rational transfer function of continuous part.